PENGARUH INOVASI LAYANAN JASA TERHADAP KEPUTUSAN PENGGUNAAN JASA PENGIRIMAN POS INDONESIA - Anggia tasya putri; Hartelina (Universitas Sarjanawiyata Tamansiswa, 2022)
Pos Indonesia, whose company's financial condition was disrupted because it was unable to compete with other competitors. Pos Indonesia has made various innovations in various fields, but these innovations have not produced results, so Pos Indonesia is still unable to compete with other competitors. This study aims to examine the effect of service innovation on the decision to use Pos Indonesia delivery services. This research method uses quantitative methods with descriptive and verification analysis. This study collected primary data in the form of a questionnaire from 100 respondents as the research sample. The sampling technique of this research is the probability sampling technique with random sampling. This study uses data analysis techniques using simple regression analysis with IBM SPSS Statistic 21 software tools. The results show that there is a positive and significant influence between service innovation on service use decisions.